Determinants Customer Satisfaction and Implications of Interest in Buying Repeated Types of Buyers in Food Vendors Street Vendors (PMKL) in Tangerang Selatan-Banten - Lestari, Rahayu; Amelia, Lisa; Hizrian, Alvin (International Review of Management and Marketing, 2018)
This research to test determinan customer satisfaction and implications of interest in buying repeated types of buyers in food vendors street vendors (PMKL) in the Tangerang Selatan.The study is done at 200 people consumers who makes a purchase food in food vendors street vendors (PMKL) in Tangerang Selatan-Banten. Research test determinan customer satisfaction and implications of interest in buying repeated types of buyers in food vendors street vendors (PMKL) in Tangerang Selatan-Banten.Data analyzed to research this in a partial least square (PLS) and used tools smartpls3.The research results show that all three variable the product quality, and in location of economic activities significant to customer satisfaction, while variable perception price has not been affecting the customer satisfaction.Variable customer satisfaction significant to interest in buying repeated consumers the food vendors the street vendors in the Tangerang Selatan-Banten. Keywords: Product quality, perception of price, location of business, customer satisfaction, interest to buying repeated, food trader sidewalk (PMKL) JEL Classifications: M31, M21, M10